ChemInform Abstract: Laser‐Induced Electronic and Nuclear Coherent Motions in Chiral Aromatic Molecules. Issue 43 (7th October 2013) - Kanno, Manabu; Kono, Hirohiko; Lin, Sheng H.; Fujimura, Yuichi
Abstract Review: 52 refs.